The title: The contributions of Recreational sports Physical Activity in improving the Quality of Life among university student’s resident. A Comparative Field Study at University Residence 19 May 1956 (Riyadh) - Males of - Aberkane, Mohammed; Zahoui, Nacer (sports creativity, 2024)
This study aimed to identify the differences in the quality of life among male university students who practice recreational physical sports activity and those who do not within the University Residence 19 May 1956 (Riyadh), employing a comparative descriptive approach. The study sample consisted of 28 resident students, 14 of whom practiced recreational physical activities within the residence and 14 of whom did not. The researchers used the UNESCO Quality of Life Scale, adapted and standardized for the Algerian environment by the researchers "Fatima Hamza" and "Hussein Boudaoud", as a study tool. The results extracted from the study indicated that there are statistically significant differences between students who do and do not practice physical recreational activity in all dimensions of the quality of life scale.